CUMULATIVE GENERAL LEDGER THE TOBACCO INSTITUTE INC. PERIOD ENDING 12-31-88 (Tufts Archival Research Center, 2007)
Confidential; Cumulative general ledger for the Tobacco Institute for period ending 12/31/88 Summarizes the debt for various vendors. Lists the check number, the debt owed, the credit issued for each vendor and the closing balance.